Programmed cell death (PCD): an essential process of cereal seed development and germination - Domínguez, Fernando; Cejudo, Francisco J. (Frontiers in Plant Science, 2014)
The life cycle of cereal seeds can be divided into two phases, development and germination, separated by a quiescent period. Seed development and germination require the growth and differentiation of new tissues, but also the ordered disappearance of cells, which takes place by a process of programmed cell death (PCD). For this reason, cereal seeds have become excellent model systems for the study of developmental PCD in plants. At early stages of seed development, maternal tissues such as the nucellus, the pericarp and the nucellar projections undergo a progressive degeneration by PCD, which allows the remobilization of their cellular contents for nourishing new filial tissues such as the embryo and the endosperm. At a later stage, during seed maturation, the endosperm undergoes PCD, but these cells remain intact in the mature grain and their contents will not be remobilized until germination. Thus, the only tissues that remain alive when seed development is completed are the embryo axis, the scutellum and the aleurone layer. In germinating seeds, both the scutellum and the aleurone layer play essential roles in producing the hydrolytic enzymes for the mobilization of the storage compounds of the starchy endosperm, which serve to support early seedling growth. Once this function is completed, scutellum and aleurone cells undergo PCD; their contents being used to support the growth of the germinated embryo. PCD occurs with tightly controlled spatial-temporal patterns allowing coordinated fluxes of nutrients between the different seed tissues. In this review, we will summarize the current knowledge of the tissues undergoing PCD in developing and germinating cereal seeds, focussing on the biochemical features of the process. The effect of hormones and redox regulation on PCD control will be discussed.